Poor Sleep Quality, Psychological Distress, and the Buffering Effect of Mindfulness Training During Pregnancy. Issue 6 (2nd November 2018) - Felder, Jennifer N.; Laraia, Barbara; Coleman-Phox, Kimberly; Bush, Nicole; Suresh, Madhuvanthi; Thomas, Melanie; Adler, Nancy; Epel, Elissa; Prather, Aric A.
ABSTRACT: Objective/Background : Poor sleep quality is common in pregnancy and associated with increased psychological distress, which has adverse consequences for families. Emerging theory suggests that mindfulness-based interventions may help reduce cognitive and emotional reactivity to stressful events. The current study examines the effects of a mindfulness-based intervention on the relationship between poor sleep quality and increased depression symptom severity and perceived stress during pregnancy. Additionally, we explored the prevalence of poor sleep quality in this unique sample and the impact of intervention on sleep quality. Participants : Participants were 215 ethnically diverse, overweight and obese, predominantly low-income pregnant women drawn from a study examining the impact of an 8-week mindfulness-based program (Mindful Moms Training; MMT) to reduce excessive gestational weight gain, stress, and depression compared to treatment as usual (TAU). Methods : Participants reported global sleep quality, depressive symptoms, and perceived stress at baseline and postintervention. Results : Most participants (63%) were categorized as poor sleepers at baseline. MMT participants did not experience significantly greater improvement in sleep quality compared to TAU participants. Baseline poor global sleep quality predicted increased depression symptom severity for all participants. Baseline poor global sleep quality predicted increased perceived stress for the TAU group only; this association was not evident in the MMT group. Conclusions : Poor sleep quality is prevalent in overweight and obese predominantly low-income pregnant women. Poor sleep quality was associated with worsening psychological distress, but mindfulness training significantly attenuated the influence of poor sleep on perceived stress.